INFLUENCE OF ADVERTISING AS A MARKETING TOOL ON CONSUMER BEHAVIOR - HROMOVA, Olha; ABDULLAEVA, Anastasiya; SHPAK, Valeriya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the main aspects of the influence of advertising as a marketing tool on consumer behavior, its types, and its meaning. The advantages and disadvantages of advertising methods are determined with the aim of studying them as an effective marketing tool. The advantages of implementing Internet advertisements have been established. Particular attention is paid to the study of modern trends. Examples of global experience in the use of advertising are given. Thus, in today’s world, advertising is undoubtedly one of the main drivers of trade. It helps to learn about new products and services, to navigate in the boundless sea of production and consumption. Advertising is a targeted informational influence of an indirect nature on consumers with the aim of promoting goods and services on the market. Without advertising, it is impossible to form broad markets for the sale of goods, to transform potentially existing needs of a certain target audience into intensive demand. The effectiveness of advertising influence on the consciousness of consumers largely depends on the extent to which it takes into account the peculiarities of human mental processes. The threshold of perception is different for different people, besides, it differs in one person at different times of the day. Symbols that one perceives only at the level of consciousness can be perceived by others quite consciously. Increasing the effectiveness of advertising and its psychological impact is one of the current tasks, and there are still many unused reserves and opportunities. In order to influence the consumer’s consciousness, it is necessary, first of all, to attract his attention, which is the first link in the chain of psychological influence of advertising. Attention itself accompanies such psychological processes as perception of advertising information by the buyer and its processing in consciousness.